2016
DOI: 10.1371/journal.pone.0155657
|View full text |Cite
|
Sign up to set email alerts
|

OBE3 and WUS Interaction in Shoot Meristem Stem Cell Regulation

Abstract: The stem cells in the shoot apical meristem (SAM) are the origin of all above ground tissues in plants. In Arabidopsis thaliana, shoot meristem stem cells are maintained by the homeobox transcription factor gene WUS (WUSCHEL) that is expressed in cells of the organizing center underneath the stem cells. In order to identify factors that operate together with WUS in stem cell maintenance, we performed an EMS mutant screen for modifiers of the hypomorphic wus-6 allele. We isolated the oberon3-2 (obe3-2) mutant t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 37 publications
(32 reference statements)
1
13
0
Order By: Relevance
“…Judging from the protein domains and sub-nuclear localization, we hypothesize that SMXL3/4/5 and OBE3 form a protein complex that is involved in chromatin remodeling and/or transcriptional regulation of downstream targets. Similar to the previous report on the OBE3-WUS interaction in the SAM (Lin et al 2016), we cannot rule out that other OBE family members apart from OBE3 interact with SMXL3/4/5 in protophloem formation. Although all mutant alleles used in this study were reported to be functional knock-outs because multiple mutants show strong embryonic defects Saiga et al 2012), residual activity of the OBE1, OBE2 or OBE4 genes might be sufficient to support SMXL3/4/5 activity.…”
Section: A Putative Role Of a Smxl3/4/5/obe3 Protein Complex In Chromsupporting
confidence: 66%
See 1 more Smart Citation
“…Judging from the protein domains and sub-nuclear localization, we hypothesize that SMXL3/4/5 and OBE3 form a protein complex that is involved in chromatin remodeling and/or transcriptional regulation of downstream targets. Similar to the previous report on the OBE3-WUS interaction in the SAM (Lin et al 2016), we cannot rule out that other OBE family members apart from OBE3 interact with SMXL3/4/5 in protophloem formation. Although all mutant alleles used in this study were reported to be functional knock-outs because multiple mutants show strong embryonic defects Saiga et al 2012), residual activity of the OBE1, OBE2 or OBE4 genes might be sufficient to support SMXL3/4/5 activity.…”
Section: A Putative Role Of a Smxl3/4/5/obe3 Protein Complex In Chromsupporting
confidence: 66%
“…In contrast to SMXL proteins whose activity is spatially highly restricted, OBERONs (OBEs) are a family of four ubiquitously expressed, nuclear-localized proteins essential for tissue specification and meristem maintenance starting from the earliest stages of embryo development (Saiga et al 2008;Thomas et al 2009;Saiga et al 2012;Lin et al 2016). This role is reflected by mutants deficient for either of the two OBE sub-families which are embryo lethal (Saiga et al 2008;Thomas et al 2009;Saiga et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…CLE peptides are a well-known group of post-translationally modified signal molecules involved in cell division in SAM, the root apical meristem (RAM) and vascular meristem, which can respond to stress signals [ 10 , 33 , 34 ]. Previous reports have demonstrated that AtWUS, AtWOX4, AtWOX5 and AtWOX14 can regulate cell division in SAM, vascular meristem and RAM [ 10 , 35 ], respectively, while WUS–CLV interactions were shown to establish a feedback loop between stem cells and the underlying regulatory center [ 7 ]. In addition, the results of the present study showed that AtWOXs could interact with some TFs, such as GRAS, SCR and SHR ( Table S7 ).…”
Section: Resultsmentioning
confidence: 99%
“…The interaction between VPg and OBE1 (an evolutionarily conserved hub in the host proteome) is suggestive, as this protein is involved in the establishment and maintenance of the shoot and root apical meristems through the regulation of the expression of the stem cell factor WUSCHEL (WUS). Notice that VPg also interacts with the PDH fingers OBERON 2 (OBE2), an element that functions like OBE1 [71], and OBERON 3 (OBE3), one of the transcriptional activators of WUS and the CLAVATA (CLV) pathway [72]. By looking at the interactors of OBE1 in the network, we found OBE3, STOMATAL CLOSURE-RELATED ACTIN BINDING 1 (SCAB1), which stabilizes actin filaments and controls stomatal movement [73], and various WRKY transcription factors, which activate the expression of defense genes against pathogens [74].…”
Section: Discussionmentioning
confidence: 99%